PHARMACOLOGY OF QUERCETIN IN DIABETIC NEPHROPATHY: A NARRATIVE REVIEW OF PRECLINICAL EVIDENCE - Ni Luh Wisma Eka Yanti (Journal of Scientech Research and Development, 2025)
Diabetic Nephropathy (DN) is a leading cause of end-stage renal disease, characterized by progressive and often irreversible collapse of renal architecture. Given the complex cellular dysfunction involved, therapeutic strategies are shifting toward integrative approaches utilizing compounds with pleiotropic effects. Quercetin is recognized as a pleiotropic molecule capable of exerting diverse and simultaneous biological effects, positioning it as a novel target-based pharmacotherapy for DN management. This narrative review evaluates the pharmacological potential of quercetin as a therapeutic agent for DN, encompassing both in vivo animal models and in vitro cell cultures. Current evidence demonstrates that quercetin effectively mitigates the multifaceted pathogenesis of DN. Key mechanisms include the attenuation of oxidative stress via the Nrf2/HO-1 signaling pathway, the inhibition of ferroptosis, and the suppression of inflammatory markers trough the regulation of NFkB and NLRP3 axis. Furthermore, quercetin preserves renal architecture by preventing podocyte apoptosis, reducing fibrosis, and restoring lipid metabolism dysregulation. Although its clinical application is currently challenged by low oral bioavailability, advanced delivery system such as nanoparticles and liposomes shows significant promise in enhancing therapeutic outcomes.